Mayer-Rokitansky-Kuster-Hauser syndrome and ovarian benign teratoma: a case report - Adjoby, Cassou R.; Koffi, Soh V.; Effoh, Denis; Lagaud, Eleonore Gbary; Alla, Christian H.; Loba, Okoin P. J.; Abauleth, Yao R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Mayer-Rokitansky-Kuster-Hauser syndrome (MRKH) is an unknown congenital etiology disorder characterized by agenesia or hypoplasia of the Müller ductal system, including the upper vagina, uterus and fallopian tubes. The occurrence of an associated ovarian tumor is rare, with fewer than 20 cases reported to date according to the literature. We report the case of a 14-year-old girl, virgin, who had not yet seen her menarche, complaining of an abdomino-pelvic mass associated with pain. The ultrasound performed revealed a large left ovarian tumor and an absence of uterus. The indication of a laparotomy confirmed the ovarian mass and a complete absence of uterus associated with vaginal hypoplasia. The contralateral ovary was present, and of normal appearance. The pathological examination was in favor of a mature benign multi-tissular teratoma. This is the first case described in our service. The mode of transmission of this entity appears to be autosomal dominant with low penetrance and variable expressivity, suggesting that the incidence of this syndrome is likely underestimated. With the development of techniques of medical assistance to procreation, maternity remains possible, particularly through gestational surrogacy.